The genome sequence of a ground beetle, Harpalus rufipes (DeGeer, 1774) [version 1; peer review: 2 approved] - Maxwell V. L. Barclay; Clive R. Turner (Wellcome Open Research)
We present a genome assembly from an individual male Harpalus rufipes (a ground beetle; Arthropoda; Insecta; Coleoptera; Carabidae). The genome sequence spans 890.50 megabases. Most of the assembly is scaffolded into 19 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 17.37 kilobases in length. Gene annotation of this assembly on Ensembl identified 13,884 protein-coding genes.